The Luganda Edinburgh Postnatal depression scale: cross-cultural adaptation and validation for prenatal screening of depression in a Ugandan sample - Mukasa, David Christopher; Ononge, Sam; Namagembe, Imelda; Byamugisha, Josaphat; Sekikubo, Musa; Muyingo, Mark; Nakasujja, Noeline (African Journals Online (AJOL), 2025)
Background: Depression affects approximately 364 million people globally. Prenatal depression affects between 26.3% and 32.9% of mothers in Africa. Opportunities for prenatal screening are missed. The gold standard diagnostic, the Diagnostic and Statistical Manual of Mental Disorders-Fifth edition (DSM-5) criteria for Major Depressive Disorder (MDD) has higher technical requirement. There is inadequate information on locally adapted and validated user-friendly screening tools in Uganda. Objective: To Adapt and validate the Luganda Edinburgh Postnatal Depression Scale (EPDS-L) for screening prenatal depression at Kawempe National Referral hospital (KNRH). Methods: Cross-sectional study in KNRH using International Society for Pharmacoeconomics and Outcomes Research guidelines for adaptation and quantitative approaches for the validation. Consecutive sampling until the desired sample of 100, all participants responded to both EPDS-L and DSM-5 criteria for MDD. Reliability demonstrated using Cronbach’s alpha coefficient, while validity was demonstrated by sensitivity, specificity, Negative Predictive Value (NPV), Positive Predictive Value (PPV) and Area-Under-the-curve (AUC). Results: EPDS-L had Cronbach’s-Alpha of 0.8515. At cut-off of 13, sensitivity was 62.86%, specificity-100%, PPV-100% and NPV-83.3%. AUC was 0.99. Performance was better at cut-off of 10, with sensitivity-97.14% and specificity-98.46%. Conclusion: The EPDS-L is reliable at cut-off of 13 but performs even better at cut-off of 10. Keywords: Mental health; prenatal depression; Edinburgh Postnatal Depression Scale; Luganda.